2017
DOI: 10.1371/journal.pone.0175112
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive characterization of DNA methylation changes in Fuchs endothelial corneal dystrophy

Abstract: Transparency of the human cornea is necessary for vision. Fuchs Endothelial Corneal Dystrophy (FECD) is a bilateral, heritable degeneration of the corneal endothelium, and a leading indication for corneal transplantation in developed countries. While the early onset, and rarer, form of FECD has been linked to COL8A2 mutations, the more common, late onset form of FECD has genetic mutations linked to only a minority of cases. Epigenetic modifications that occur in FECD are unknown. Here, we report on and compare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
44
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(47 citation statements)
references
References 70 publications
0
44
2
Order By: Relevance
“…Together, these data show that the majority of differentially methylated miRNA probes occur in intragenic and intronic sequences of their host genes. Our prior genome-scale analysis of the DNA methylation landscape of corneal endothelial tissue found a significant difference between FECD and normal control patients [30].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Together, these data show that the majority of differentially methylated miRNA probes occur in intragenic and intronic sequences of their host genes. Our prior genome-scale analysis of the DNA methylation landscape of corneal endothelial tissue found a significant difference between FECD and normal control patients [30].…”
Section: Resultsmentioning
confidence: 99%
“…To validate and quantify miRNA DNA hypermethylation changes identified by the global array [30], MethyLight analysis was performed on an additional cohort of control and FECD patient corneal samples (Table 3) [42]. MethyLight assessed the promoter DNA methylation status of following miRNAs: miR-199A1, miR-874, miR-140, miR-23B, and miR-1306 ( Fig S1, Table S1 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Following a comprehensive systematic review of the literature, this study found that the role of methylation in ophthalmic disease has been evaluated in histone methylation marks,41–43 gene body and promoter regions,44–53 and miRNAs,54 in the following rare ophthalmic conditions:…”
Section: Discussionmentioning
confidence: 99%